Deep learning-based automated thrombolysis in cerebral infarction scoring: a timely proof-of-principle study - Nielsen, Maximilian; Waldmann, Moritz; Frölich, Andreas M. J.; Flottmann, Fabian; Hristova, Evelin; Bendszus, Martin; Seker, Fatih; Fiehler, Jens; Sentker, Thilo; Werner, René (Stroke, 2021)
Download figureDownload PowerPoint